The Function of the Police in Preventing the Escalation of Riots through a Humanistic Approach Based on Law No. 2 of 2002 - Rangga Monicho Ramadhan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the function of the police in preventing the escalation of riots through a humanistic approach based on Law Number 2 of 2002 concerning the Indonesian National Police. The research method used is normative juridical with a descriptive qualitative approach, focusing on the analysis of legal norms, human rights principles, and the implementation of humanistic values in policing practices. The results show that a humanistic approach is effective in reducing the potential for social conflict through communication, mediation, and community partnerships. Its effectiveness is determined by the professionalism of officers, ethical leadership, organizational culture, as well as policy support and public trust. The application of a humanistic approach strengthens the legitimacy of the Indonesian National Police as protectors of society who uphold justice and human right. This study emphasizes the importance of institutional reform and the enhancement of human resource capacity to realize policing that is humanistic and democratic in Indonesia.